Review Penggunaan Obat Rawat Jalan Peserta Askes Sosial di RSMH Palembang selama Tahun 2007 Pemberdayaan Masyarakat Bidang Kesehatan di Era Otonomi Daerah - Sarmalina S., Sonlimar M. (Fakultas Kedokteran Universitas Gadjah Mada, 2008)
Background: Since 1987 PT Askes has been implementing the drug usage guideline which is called DPHO (Daftar dan Plafon Harga Obat).In order to encourage drug services efficiently and related to medical needs. In addition PT Askes has got benefits in medicine expenses that can lower it up to 40%. Although it has better guidence as long as implementations without being control continuously the aim of it can be far from hope. Through this study we want to examine how extent the drug usage in social health insurance.Method: In this paper we used cross-sectional study, using entry data base prescriptions from the entire social health insurance participant related in to the first care outpatient and advanced care outpatient. All of the patients originally based on polyclinics hospital services in RSMH during 2007. All of prescriptions we used as data resources. All these data were observed and analyzed performed in descriptive and tabulation.Results: The result of this study shows that we got 140.256 pieces of per encounter during 2007 with total cost Rp10.657.075.126,00. The average cost per encounter is Rp75.983,00 range from Rp231,00 to Rp5.151.227,00. The average number of drug per encounter is 4,4 and the percentage drug used of antibiotics is 10,81%.Conclusion: This study comes to conclusion that the prescriptions costs in social health insurance outpatient was high enough. It is cost by certain prescriptions, polifarmacy, and diverse drugs usage in overuse prescribing category such as vitamin neurotropic and drug used in AH2 receptor blocker like as ranitidin that has been prescribed for alleviating gastrointestinal effect.Keywords: drug utilities, social health insurance, health care, outpatient